FAKTOR-FAKTOR YANG MEMENGARUHI CASH HOLDING - Sugihwan, Bryan Adithya; Susanto, Liana (Jurnal Paradigma Akuntansi, 2024)
This study aims to obtain empirical evidence about the effect of leverage, firm size, profitability, and capital expenditure on cash holding in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The number of samples in this study was selected by purposive sampling method and the valid data were 78 companies. The research data were analyzed using multiple linear regression analysis techniques which were processed with Eviews12 SV software. The results of this study indicate that profitability and capital expenditure have a significant positive effect on cash holding. Firm size does not have a significant effect on cash holding. Leverage has a significant negative effect on cash holding.